Accumulation and Potential Ecological Risk Assessment of Heavy Metals in surface sediments of Han River Estuary, Da Nang City - Trinh, Le Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4667, 2017)
Deposited sediments contain toxic metals which can pollute surface water as well as aquatic eco-systems. Accumulation of heavy metals in sediment was assessed based on the geoaccumulation index (Igeo), the degree of contamination (C d value) and potential ecological risk was also proposed based on ecological risk index (RI). The surface sediments collected at Han river estuary, Da Nang city were digested with a mixture of HNO 3 nd H 2 O 2 , and analyzed for five heavy metals Cd, Cr, Cu, Pb and Zn sing inductively coupled plasma-atomic emission spectroscopy (ICP-AES), separately using the AAS method for AS .Â  Results showed that all of metals were detected in sediment samples with mean concentration of As, Cd, Cr, Cu, Pb and Zn were 9.16; 0.083; 52.5; 45.4; 23.2 and 41.1 mg/kg dw, in respective. C d values were smaller than 8 suggested that surface sediments of Han river estuary were moderately polluted by this metal.Â  Besides, the results of potential ecological risk factor show that the risks of heavy metals are in the decreasing order of Cu>Pb>As>Cr>Cd>Zn.